« C’est du bricolage » ou l’envers d’une métaphore artistique - Claire Le Thomas (Images Re-Vues)
In French, it is very common to use the word bricolage to describe contemporary work of art. What does this metaphor mean? On which principles does it leans? In what ways this comparison opens new leads to analyze art’s practices and materiality or to understand creation’s modus operandi? A first level of interpretation shows that this metaphor is supported by a strong similarity between artistic practices and sociological uses of bricolage. Thus, it reveals that artist and ordinary peoples share a technical and material culture. Practices moves from one field of human activity to another, between “art worlds” to use Howard Becker expression, just as shown by the cubist example. Nevertheless, following Claude Levi-Strauss thinking, bricolage is more a specific manner to create, half way between artistic and scientific method, than a material culture with its historical and sociological specificities. This second level of interpretation can be extended when looking at creation from a larger point of view. Levi-Strauss’ description of the bricoleur’s method can apply to any kind of creation. Therefore, bricolage is a metaphor unveiling the mechanism of creating.